2022
DOI: 10.1097/mpg.0000000000003588
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Mast Cells in Gastrointestinal Biopsies in Pediatric Irritable Bowel Patients

Abstract: Objectives: Mast cells (MCs) have been proposed to be involved in the pathophysiology of irritable bowel syndrome (IBS). Nonetheless, the quantity and distribution of MCs in the gastrointestinal tract of pediatric patients with IBS are not well defined. This study aimed to compare the number of MCs in children with and without IBS and to establish histopathological reference values in pediatrics. Methods: Forty-nine participants with IBS were prospectively enrolled and classified into IBS with atopy (n = 29) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The findings in these and several other studies 27,[32][33][34][35][36] that report mean mast cell counts in excess of 20/hpf at various sites in the GI tract suggest that (1) the proposed upper limit of normal of 20/HPF for mast cells in GI biopsies is not applicable to biopsies stained with CD117, and (2) there is insufficient evidence to support mast cell counting in GI biopsies as part of the diagnostic work-up for chronic diarrhoea with no identified underlying cause.…”
Section: Mast Cell Activation Syndromesupporting
confidence: 68%
See 1 more Smart Citation
“…The findings in these and several other studies 27,[32][33][34][35][36] that report mean mast cell counts in excess of 20/hpf at various sites in the GI tract suggest that (1) the proposed upper limit of normal of 20/HPF for mast cells in GI biopsies is not applicable to biopsies stained with CD117, and (2) there is insufficient evidence to support mast cell counting in GI biopsies as part of the diagnostic work-up for chronic diarrhoea with no identified underlying cause.…”
Section: Mast Cell Activation Syndromesupporting
confidence: 68%
“…42 Owing to their key role as inflammatory mediators and maintenance of normal gut function, mast cell numbers in GI biopsies have been extensively evaluated in IBS. Interestingly, a number of studies have reported an increased number of mucosal mast cells in patients with IBS relative to asymptomatic controls [34][35][36][37][38][39][40][41] ; indeed, in a large pooled meta-analysis of 22 studies, mast cells were found to be significantly increased in the descending (standardised mean difference [SMD]: 1.69 [95% confidence interval [CI]: 0.65-2.73]; P = 0.001) and rectosigmoid (SMD: 0.38 [95% CI: 0.06-0.71]; P = 0.02). 42 The large overlap in counts between patients with IBS and normal controls, however, limits the diagnostic utility of this observation, and other studies have found no significant differences in mast cell counts between patients with IBS and healthy controls.…”
Section: Mast Cell Activation Syndromementioning
confidence: 99%
“…Mast cells have also been described in IBS. In a retrospective cohort study including 49 pediatric patients with IBS and 42 control patients, patients with IBS had a statistically significant increase of mast cells within the stomach, duodenum, terminal ileum, and descending colon, independent of systemic atopy [9 ▪ ].…”
Section: Potential Causes and Risk Factorsmentioning
confidence: 99%
“…IBS has been described as one type of FABD, along with functional dyspepsia, abdominal migraines and functional abdominal pain not otherwise specified (FAP-NOS), also termed disorders of gut-brain interactions (DGBIs) [3,4 ]. According to the Rome IV Pediatric Committee, IBS must include the following for at least 2 months prior to diagnosis: abdominal pain for at least 4 days out of a month associated with either defecation, a change in frequency of stools or appearance of stool; pain that is not relieved by defecation; and symptoms that cannot be explained by another condition after thorough evaluation.…”
Section: Defining Criteriamentioning
confidence: 99%
See 1 more Smart Citation